Normative Values of Brainstem Auditory-Evoked Responses in Sheep - Katharina Suntinger; Adrian Dalbert; Lukas Prochazka; Milena Tegelkamp; Peter Kronen; Karina Klein; Christof Röösli; Alexander Huber; Flurin Pfiffner (Brain Sciences)
Background: The brainstem auditory-evoked response (BAER) is an established electrophysiological measure of neural activity from the auditory nerve up to the brain stem. The BAER is used to diagnose abnormalities in auditory pathways and in neurophysiological human and animal research. However, normative data for BAERs in sheep, which represent an adequate large animal model for translational and basic otological research, are lacking. Objective: The aim of this study was to assess the function of the ovine auditory nervous system by determining normative values for the BAER and to compare sheep with human BAER data. Methods: In this retrospective study, BAER data for click stimuli at a range of sound pressure levels (SPLs) were analyzed. A series of 15 samples from six sheep with a mean age of 41.8 months was included. Results: The mean BAER threshold was 45.3 dB SPL. At 100 dB SPL, the mean (±standard deviation, SD) latency of wave V was 4.35 (±0.18) ms, that of wave III was 2.44 (±0.15) ms, and that of wave I was 0.88 (±0.13) ms. At 100 dB SPL, the mean interpeak latency of waves I–III was 1.56 (±0.18) ms, that of waves III–V was 1.91 (±0.16) ms, and that of waves I–V was 3.47 (±0.20) ms. The mean amplitudes at 100 dB SPL were 0.04 (±0.03) µV for wave I, 0.50 (±0.24) µV for wave III, and 0.40 (±0.25) µV for wave V. Conclusions: The normative values for sheep BAERs were reproducible and similar to those of humans. The normative BAER values further support sheep as an adequate animal model for otological research.